PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL PADA MATERI SENAM LANTAI SISWA KELAS VII SMP NEGERI B SRIKATON - Yanti, Yuli; Darsi, Helvi; Syafutra, Wawan (Jurnal Tunas Pendidikan, 2023)
ABSTRACT This study aims to develop audio-visual learning on floor exercise in subjects PJOK at SMP Negeri B Srikaton. Which can be used to support learning. The learning media made is in the form of audio visual to determine the quality of the audio visual seen from the aspects of validity and practicality. This research was conducted at SMP Negeri B Srikaton. This study aims to develop an audio-visual on floor exercise material and to determine the quality of the audio visual in terms of validity and practicality. This research is a development research that refers to the ADDIE development model, namely Analyze, Design, Development, Implement, Evaluate. The instrument used to measure the quality of the audio visual developed includes a validation sheet and a practicality sheet. The validation sheet is filled in by experts (linguists, material experts, and media experts). While the practicality sheet was filled out by students in individual tests (one to one test) and small group tests (small group test). The product of this research is in the form of audio visuals on the floor exercise material for class VII SMP. The results showed that: (1) the audio visual quality seen from the validity aspect was included in the valid category with an average score of 3.05 and (2) the audio-visual quality seen from the practical aspect is categorized as practical with an average score of 3.27. Keywords: Audio Visual Media, Learning, Floor Gymnastics